Media Pembelajaran Digital Interaktif : Upaya Penguatan Konsep Matematika Peserta Didik - Anjelina Surat Lelan; Ni Kadek Rini Purwati; I Gusti Agung Gede Wiadnyana (Griya Journal of Mathematics Education and Application, 2025)
Low conceptual understanding in mathematics remains a significant challenge in the learning process and highlights the need for more effective and innovative pedagogical strategies. This issue is often caused by conventional teaching practices and the limited use of learning media in schools, leading students to develop negative attitudes toward mathematics and resulting in weak conceptual understanding. This study aims to develop a mathematics learning medium in the form of the Debar application, designed with Construct 3 for SMA/SMK. The research employed a Research and Development (R&D) approach using the ADDIE model. Data were collected from expert validators, mathematics teachers, and tenth-grade students at SMK PGRI 1 Denpasar through questionnaires and tests. The validation results showed that the Debar application was categorized as “very valid”. The practicality test indicated that the application was “practical”. Furthermore, the effectiveness test revealed that the students’ learning mastery percentage reached 86.7%. Based on these findings, it can be concluded that the Debar application meets the criteria of being valid, practical, and effective, thus making it feasible to be used as a mathematics learning medium that facilitates the reinforcement of students’ conceptual understanding. The validation test results showed that the Debar application was categorized as “very valid.” The practicality test also indicated that the application was “practical.” Meanwhile, the effectiveness test results revealed that the percentage of students’ learning mastery reached 86.7%. Thus, it can be concluded that the Debar application meets the criteria of being valid, practical, and effective, as well as providing psychological support in the mathematics learning process, thereby serving as a learning medium that facilitates the strengthening of students’ conceptual understanding. Moreover, engaging in learning media can foster students’ positive attitudes toward mathematics.